The possible mechanisms of ferroptosis in sepsis-associated acquired weakness - Yang, Jun; Yan, Caihong; Chen, Shaolin; Li, Min; Miao, Yanmei; Ma, Xinglong; Zeng, Junfa; Xie, Peng (Frontiers in Physiology, 2024)
Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection, and its morbidity and mortality rates are increasing annually. It is an independent risk factor for intensive care unit-acquired weakness (ICU-AW), which is a common complication of patients in ICU. This situation is also known as sepsis-associated acquired weakness (SAW), and it can be a complication in more than 60% of patients with sepsis. The outcomes of SAW are often prolonged mechanical ventilation, extended hospital stays, and increased morbidity and mortality of patients in ICUs. The pathogenesis of SAW is unclear, and an effective clinical treatment is not available. Ferroptosis is an iron-dependent type of cell death with unique morphological, biochemical, and genetic features. Unlike other forms of cell death such as autophagy, apoptosis, and necrosis, ferroptosis is primarily driven by lipid peroxidation.Cells undergo ferroptosis during sepsis, which further enhances the inflammatory response. This process leads to increased cell death, as well as multi-organ dysfunction and failure. Recently, there have been sporadic reports suggesting that SAW is associated with ferroptosis, but the exact pathophysiological mechanisms remain unclear. Therefore, we reviewed the possible pathogenesis of ferroptosis that leads to SAW and offer new strategies to prevent and treat SAW.